Making Decentralization Work in The Philippines: The experience of Canada-Philippines Partnership Program - Francis E. Gentoral (Journal of Regional and City Planning, 2004)
A multi-stake holder strategy development and project implementation capacity development program facilitated by the Canadian Urban Institute in the Guimaras Province and replicated in Metropolitan Iloilo region and Boracay island, Philippines have resulted in local governments units embracing their responsibilities associated with decentralization more efficiently, effectively and democratically, abiding by principles of sustainable development. Optimizing limited resources, substantial improvements in solid waste management, ecotourism and agro-industry at the local and provincial levels have also been achieved over the course of 8 years